Walking as a Foundation for Community Asset Building: Evaluating Social Cohesion and Wellbeing Through ABCD (Baltic Journal of Sport and Health Sciences, 2026)
Walking is a fundamental yet underutilised lever for improving public health and social cohesion. While infrastructure often dominates policy discourse, walking can be a vehicle for strengthening community connections, particularly when embedded within asset-based approaches. This study evaluates how Beat the Street (BTS), a gamified walking intervention, fosters community development through the Asset-Based Community Development (ABCD) model, offering a replicable framework for place-based health promotion.The study included six United Kingdom locations where BTS took place, engaging residents through RFID-enabled ‘Beat Boxes’ placed across local areas. The intervention promotes inclusive participation, especially in deprived communities. A total of 1,503 matched participants completed pre- and post-surveys measuring ABCD Maturity – encompassing trust, social capital, engagement with public spaces, and cultural storytelling – and the Health Creation Index (HCI), a composite wellbeing metric.Post-intervention, physical activity levels rose by 10.2 percentage points (to 66.0%). Gains in social cohesion included increased trust in local institutions (+7.45 pp) and feeling part of a local network (+5.85 pp). Cultural belonging improved markedly, with a (7.77) pp increase in participants affirming they had stories reflecting their community’s heritage. Deprived groups showed the largest gains in network belonging (+7.85 pp) and cultural storytelling (+9.13 pp). Those with higher HCI scores also reported stronger ABCD Maturity, especially those who previously lacked a sense of belonging (+11.9 pp increase in network connection).These results highlight the power of walking to catalyse social and cultural engagement. Community-led walking initiatives can generate meaningful public health gains beyond individual behaviour change by nurturing inclusive, resilient environments. Embedding ABCD frameworks into walking policy can support equity-focused investment in areas with untapped community potential.